Initial experience of coronary angiogram through trans ulnar route in Bangabandhu Sheikh Mujib Medical University - Salim, Md Abu; Ahsan, Syed Ali; Siddique, Md Abu; Banerjee, Sajal Krishna; Rahman, AKM Fazlur; Ahmed, CM; Hoque, Harisul; Shafiuddin, Md; Zaman, SM Mustafa; Habib, Ahsan; Adhikary, Dipal Krishna; Arju, Jahanara; et al. (University Heart Journal, 2015)
For performing Coronary angiogram and PCI Trans ulnar route is a feasible alternate access. It has got all the advantages of transradial route. Beside that by this approach radial artery can be spared to be used as a conduit for subsequent surgical revascularization. The hardware used for both transulnar and transradial routes are similar. In our study technical success rate is 93.99% through transulnar route, 6.66% case was postponed due to failure to canulate the ulnar artery. The complications such as local hematoma, significant swelling, access site bleeding, ulnar artery perforation and reversible parasthesia was nil (0% of patients). Post procedure asymptomatic ulnar artery occlusion did not occur. University Heart Journal Vol. 9, No. 2, July 2013; 80-82